An interim report of the Scleroderma Clinical Trials Consortium working groups. Issue 1 (February 2019) - Baron, Murray; Kahaleh, Bashar; Bernstein, Elana J; Chung, Lorinda; Clements, Philip J; Denton, Christopher; Domsic, Robyn T; Ferdowsi, Nava; Foeldvari, Ivan; Frech, Tracy; Gordon, Jessica K; Hudson, Marie; et al.
The Scleroderma Clinical Trials Consortium represents many of the clinical researchers in the world who are interested in improving the efficiency of clinical trials in systemic sclerosis. The Scleroderma Clinical Trials Consortium has established 11 working groups to develop and validate better ways of measuring and recording multiple aspects of this heterogeneous disease. These include groups working on arthritis, disease damage, disease activity, cardiac disease, juvenile systemic sclerosis, the gastrointestinal tract, vascular component, calcinosis, scleroderma renal crisis, interstitial lung disease, and skin measurement. Members of the Scleroderma Clinical Trials Consortium may join any one or more of these groups. Some of the working groups have only recently started their work, some are nearing completion of their mandated tasks, and others are in the midst of their projects. All these projects, which are described in this article, will help improve clinical trials and observational studies by improving or developing better, more sensitive ways of measuring various aspects of the disease. As Lord Kelvin stated, "To measure is to know. If you cannot measure it you cannot improve it." The Scleroderma Clinical Trials Consortium is dedicated to improving the lives of patients with systemic sclerosis and it is our hope that the contributions of the working groups will be one important step in this process.